The Relationship between Diabetes Mellitus and Periodontal Condition of Prolanis Patients Kersanagara Health Center, Tasikmalaya City - Sri Suharja, Eliati (Jurnal Kesehatan Gigi, 2025)
Diabetes mellitus is a chronic disease that patients suffer from throughout their lives. In the world, there are currently 422 million people with diabetes, this data has increased four times more than 30 years ago. Diabetes sufferers in Indonesia are estimated to reach 30 million people by 2030. Uncontrolled diabetes mellitus can weaken the immunity of periodontal tissue, conversely, untreated periodontal disease will worsen blood sugar balance resulting in damage to the tooth supporting tissue or periodontal tissue. Research objective: to determine the relationship between diabetes mellitus and periodontal disease in prolanis patients in the working area of the Kersanagara Health Center, Tasikmalaya City. Methodology: the method used is an analytical approach cross-sectional, population 37 person Prolanis patients with cases of diabetes mellitus, sampling using Totalsampling. Data analysis used the chi square test. Research results: the highest number of patients suffering from type 2 diabetes mellitus at Prolanis (78,4%) with periodontal tissue conditions mostly experienced deep pockets (64,9%). Chi square analysis obtained values, p-value= 0,002 (p0,05), meaning that there is a significant relationship between type 2 diabetes mellitus and periodontal conditions with deep pockets in prolanis patients at the Kersanagara Community Health Center, Tasikmalaya City. Conclusion: There is a very significant relationship between diabetes mellitus and the periodontal condition of prolanis patients at the Kersanagara Community Health Center, Tasikmalaya City.